2012
DOI: 10.1016/j.jbiomech.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Axial speed of sound is related to tendon's nonlinear elasticity

Abstract: Axial speed of sound (SOS) measurements have been successfully applied to noninvasively evaluate tendon load, while preliminary studies showed that this technique also has a potential clinical interest in the follow up of tendon injuries. The ultrasound propagation theory predicts that the SOS is determined by the effective stiffness, mass density and Poisson's ratio of the propagating medium. Tendon stiffness characterizes the tissue's mechanical quality, but it is often measured in quasi-static condition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…The axial transmission speed of ultrasound (TSOU) in tendon is proportional to its density and instantaneous material stiffness [45], which, in turn, is dependent on the applied load to the tendon [32]. Ultrasound transmission techniques take advantage of the relationship between TSOU and tendon biomechanics to afford a non-invasive method of quantifying properties of human tendon under dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The axial transmission speed of ultrasound (TSOU) in tendon is proportional to its density and instantaneous material stiffness [45], which, in turn, is dependent on the applied load to the tendon [32]. Ultrasound transmission techniques take advantage of the relationship between TSOU and tendon biomechanics to afford a non-invasive method of quantifying properties of human tendon under dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Previous strain measurement techniques are poorly adaptable to veterinary medicine because of invasiveness, necessity for unrealistic levels of patient cooperation, expense, and specialized equipment requirements. Preliminary studies of noninvasive, sonographic methods for evaluation of tendon function in veterinary species have been based on elastography, 17 measurement of the axial speed of sound, [18][19][20][21][22] or acoustoelasticity. 23,24 These techniques currently offer the greatest potential for practical clinical application in horses with tendon injury.…”
mentioning
confidence: 99%
“…Ultrasonic transmission techniques have the potential to provide direct non‐invasive estimates of human tendon loading. In vitro studies of animal tendon have demonstrated that the axial transmission of ultrasonic waves is governed by the elastic modulus and density of tendon and is a function of the tensile load to which it is exposed (Hoffmeister et al., ; Miles et al., ; Kuo et al., ; Pourcelot et al., ,b; Vergari et al., ,b,c). Recently, ultrasound transmission has also been shown to be a sensitive indicator of tendon injury in animal models and has been used to document the recovery of tendon properties following injury (Vergari et al., ,b,c).…”
mentioning
confidence: 99%
“…In vitro studies of animal tendon have demonstrated that the axial transmission of ultrasonic waves is governed by the elastic modulus and density of tendon and is a function of the tensile load to which it is exposed (Hoffmeister et al., ; Miles et al., ; Kuo et al., ; Pourcelot et al., ,b; Vergari et al., ,b,c). Recently, ultrasound transmission has also been shown to be a sensitive indicator of tendon injury in animal models and has been used to document the recovery of tendon properties following injury (Vergari et al., ,b,c). Although ultrasound transmission is emerging as a potentially useful technique for the non‐invasive of measurement of tendon properties during dynamic activities, studies employing the technique in humans have been currently limited to measurement of the Achilles tendon during walking (Pourcelot et al., ,b; Wearing et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation